PENGARUH PROMOSI DAN LAYANAN PENGUNJUNG TERHADAP PENJUALAN TIKET DI KAWASAN WISATA KEBUN RAYA BOGOR - LILIS CUCU SUMARTINI LILIS CUCU SUMARTINI (POLITEKNIK PIKSI GANESHA, 2018)
To measure how much influence between promotion and consumer service hence used method of quantitative descriptive research that is a method that measure phenomenon and current situation. Descriptive research focuses more on solving current problems, on actual issues and data collected and then compiled and analyzed. Descriptive research analysis is an approach to describe a real situation based on existing data and information.The result of measurement between promotion and visitor service found that (1) There is positive and significant influence between promotion (X1) to ticket sales (Y), shown by Ryx1 0,415 with determinative degree equal to 0,173, giving influence 17,3% (2) There is a positive and significant influence between visitor service (X2) on ticket sales (Y), which is shown by Ryx2 of 0.421 with determinative degree of 0.177, giving effect of 17,7% to ticket sales ( 3) There is a positive and significant influence between promotion (X1) and visitor service (X2) on ticket sales (Y), shown by Ryx1.2 of 0.485 with determinative degree of 0.235, giving 23.5% tickets.